A Comparative Study on the Addition of MgO and Mg(OH)2 Nanoparticles into PCL Electrospun Fibers. Issue 1 (15th August 2022) - Salaris, Valentina; Leonés, Adrián; López, Daniel; Kenny, José Maria; Peponi, Laura
Abstract: In this work, a comparative study between the morphology, the thermal and the mechanical properties of poly(ɛ‐caprolactone) (PCL)‐based electrospun fiber mats reinforced with both MgO and Mg(OH)2 nanoparticles, is carried out. Both MgO and Mg(OH)2 nanoparticles have been added in a range of concentrations such as 0.5, 1, 5, 10, 20 wt% with respect to the PCL matrix, with the aim of improving their mechanical properties in comparison with neat PCL electrospun fibers. From the morphological point of view, electrospun fibers are randomly collected and an increase in the average fiber diameter with the addition of nanoparticles is observed. The addition of both types of nanoparticles lower the onset degradation temperature as well as the maximum degradation temperature of neat ePCL of about 50 °C with the higher content of nanoparticles. Furthermore, PCL electrospun nanofiber mats show a degree of crystallinity of 53%, which is quite high. However, the addition of 20 wt% of both MgO and Mg(OH)2 lowers the crystallinity of the reinforced electrospun fibers to 50% and 43% for PCL + MgO 20 wt% and Mg(OH)2 20 wt%, respectively. Abstract : A comparative study on PCL electrospun fibers (ePCL) reinforced with both magnesium oxide (MgO) and magnesium hydroxide (Mg(OH)2 ) nanoparticles, at different concentrations as 0.5, 1, 5, 10, 20wt%, is reported. The addition of nanoparticles produces an increase in the average fiber diameter without affecting the high degree of crystallinity of the neat ePCL and induces a different reinforcing effect varying with their amount.